Assessing the Potential of Ethno-pharmaceutical Integration at Yoga Barn Ubud: A SWOT and Health Belief Model Analysis - Febryanti, Ekanur; Widowati, I Gusti Ayu Rai; Hita, I Putu Gede Adi Purwa; Setiawan, I Putu Yudhistira Budhi (PT BMW Journal Sejahtera, 2025)
Background: Ethnopharmaceuticals is a diverse field that examines how individuals perceive and utilize traditional therapies, focusing on plant-based treatments and holistic health approaches typically passed down through generations. Objective: This research aims to analyze the potential of ethnopharmaceuticals at Yoga Barn Ubud using SWOT and Health Belief Model approaches. The goal is to identify the internal and external factors impacting performance and to understand how individual health beliefs influence participation in wellness activities. Method: A qualitative exploratory approach was employed, gathering primary data through in-depth interviews with 12 participants at Yoga Barn using purposive sampling. Results: SWOT analysis revealed Yoga Barn's strengths, such as its prime location, diverse yoga classes, and positive reputation. Weaknesses included limited awareness of ethnopharmaceutical services, competition, and a focus on seasonal tourists. Opportunities highlighted growing health campaigns and connections with global health networks, while threats included traditional practices being overshadowed by modern therapies. The Health Belief Model indicated that participants' beliefs about health risks and the benefits of yoga significantly influenced their engagement in wellness activities. Conclusion: Yoga Barn in Ubud effectively integrates local wisdom, traditional herbal medicine, and meditation, creating a holistic wellness experience that attracts tourists while preserving traditional knowledge.